2016
DOI: 10.2209/tdcpublication.2016-1600
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Scissor Bite Treated by Rapid Mandibular Expansion Following Corticotomy

Abstract: Scissor bite is defined as buccal displacement of the maxillary posterior teeth, with or without contact between the lingual surface of the maxillary lingual cusp and the buccal surface of the buccal cusp of its mandibular antagonist. Here we report treatment of bilateral scissor bite in the posterior region using rapid expansion following corticotomy. The patient was a boy aged 17 years and 11 months in whom skeletal maxillary prognathism with bilateral scissor bite was diagnosed. The distance between the tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Distraction osteogenesis consists in the biological process of bone formation between preexisting bone segments that are progressively separated by controlled traction. The intermolar and intercanine distances usually remain stable after expansion, and healing/stability usually occurs within 3 to 4 months, so that the distraction device can be removed and orthodontic treatment subsequently initiated [5,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distraction osteogenesis consists in the biological process of bone formation between preexisting bone segments that are progressively separated by controlled traction. The intermolar and intercanine distances usually remain stable after expansion, and healing/stability usually occurs within 3 to 4 months, so that the distraction device can be removed and orthodontic treatment subsequently initiated [5,14].…”
Section: Discussionmentioning
confidence: 99%
“…Sakamoto et al [5] demonstrated the effectiveness of lateral mandibular expansion treatment after corticotomy in a young adult patient with a skeletal scissor bite. According to these authors, expansion by corticotomy reduces the gingival recession risk and hyperesthesia and also guarantees posttreatment stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karthikeyan et al79 treated a Class I malocclusion and open bite patient by removing the bulky anterior cortical bone and intruding the anterior teeth. Corticotomies can also be used for canine retraction5480, anterior teeth retraction, decrowding5381, molar uprighting37, correction of a scissor bite82, and rapid maxillary expansion. Lines83 introduced a method for the correction of a maxillary constriction that applied incisions on the lateral walls of the maxillary sinus and mid-palatal sutures.…”
Section: Indications and Limitationsmentioning
confidence: 99%
“…Buccal nonocclusion is defined as maxillary teeth not occluding with mandibular teeth and overlapping buccal to the mandibular arch. [1] This problem has two different etiologies: congenital or traumatic. [2] In trauma patients, this event often is related to fracture of one jaw, so correction should focus on it; however, in orthognathic patients, this results from combination of upper jaw widening and lower jaw narrowing.…”
Section: Introductionmentioning
confidence: 99%